Considerações sobre o novo sistema eletrônico de escrituração das duplicatas: análise da lei nº 13.775/2018 e do seu impacto econômico e social no Brasil - Gonçalves, Aléssio Martins (2023)
The objective of this study was to analyze the implementation, in Brazil, of the new electronic system for the bookkeeping of duplicates, provided for in Law nº 13.775/2018, and which is not yet in operation due to lack of complete government regulation, under the scientific focus of the challenges that the implementation of such a system faces. There is no doubt that the system developed by Law nº 5.474/1968, which regulates the issuance and circulation of the duplicate, over the decades, due to business and technological evolution, needed to be modernized, both in the form of use and in the form of structuring the credit instrument, but without losing its essence already much studied in national foreign exchange law. With the emergence of intangible credit titles (the so-called virtual duplicate), the legislation itself provided for the need to create an electronic bookkeeping system that would provide greater security and agility in the negotiation of credit, as well as to be able to compete in the national market with new means of payment, such as credit cards and book-entry payment (with the payment of a bank slip, for example). The implementation of such a system must reconcile the need for a modern, secure system with broad access to economic agents, with the need to observe the doctrinal and jurisprudential knowledge base on the subject, and this is the scope of the research, which is reflected in this dissertation. In the course of the research, a logical-deductive analysis of the evolution of the duplicate and its place in the general theory of credit securities is sought, allowing, at the end, an empirical analysis of the challenges of the implementation of the electronic bookkeeping system and its economic and social impact in Brazil.